The environmental fate of metals from zinc and lead mining area in surface water (Przemsza River, southern Poland) - Pierri, Dorota; Rutkowski, Marcin (Geology, Geophysics and Environment, 2022)
The chemical composition of surface waters of the Przemsza River flowing through Upper Silesia (in southern Poland) is strongly affected by Zn and Pb ore, and less by Carboniferous hard coal deposits. The chemical type of surface water is Ca-HCO3. In the waters, three groups of metals and metalloids were found that directly interfere with the mineralization of the deposit. Although genetically related to the same deposit, each group exhibits a different fate in the environment. A typical deposit association is Pb-Zn-Ag-As-Sb-Hg. The first group of metals in surface waters is consistent with the typical association of the ore Zn-Pb-Cd-(Tl), the second includes Ag-Sb-Hg, and the third includes the additives in the zinc and lead ore Co-Ni-Mo-Mn:[(Ca↔Na)+(HCO3↔Cl)]+[(Zn-Pb-Cd-(Tl))+(Ag-Sb-Hg)+Co-Ni-Mo-Mn)].Depending on the pH-Eh conditions, metals and metalloids precipitate out of the solution or sorb on solid particles. The concentrations of individual groups of metals are interdependent but show different environmental fates along the river course. The natural process of the enrichment of surface waters with Zn-Pb-Cd-(Tl) is by water circulation in a rock matrix naturally rich in the metals and draining groundwaters by the river. Under oxidizing and slightly alkaline conditions, Ag-Sb-Hg incorporated into the soluted chemical compounds, may, when the physicochemical parameters of the waters change, be adsorbed and/or precipitated. The presence and ratio of concentrations of Co-Ni-Mo-Mn with respect to zinc are almost identical, differing only in concentration.